Analisis Perilaku Komunikasi Penggemar K-Pop Melalui Komunitas Channel NCT Pada Aplikasi Weverse - Gita .; Ashar Hasyim; Nana Adriana Hutari (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2026)
This study aims to analyze the communication behavior of Pop fans through the NCT Channel community on the Weverse application in Kendari City using the Uses and Gratification theory by Herbert Blumer and Elihu Katz. The communication behavior that occurs in the NCT Channel community on Weverse is not merely a form of simple interaction, but also reflects the social and cultural dynamics within the K-Pop fandom, including the use of language, symbols, or certain expressions understood by fellow fans, as well as how fans interpret messages conveyed by idols or other community members. This study uses a descriptive qualitative method with data collection techniques through observation, in-depth interviews with six informants, and documentation of community activities. The results of the study show that the communication behavior of NCT fans in Kendari demonstrates active participation, where fans not only act as message recipients but also as parties directly involved in the communication process. It also meets their satisfaction in interacting. Activities such as commenting, waiting for updates from members, and regularly watching content reflect strong emotional engagement. In addition, the use of Weverse also fulfills the fans' entertainment, information, and affective needs, creating a sense of satisfaction and comfort in interacting on Weverse.